Determinants of family planning services uptake among women within the reproductive age in the Yendi municipality in Northern Ghana - Iddrisu Sulemana; Collins Gbeti; Maxwell Dalaba; Adadow Yidana; Gifty Apiung Aninanya (BMC Public Health)
Abstract The study investigated the prevalence and determinants of family planning services uptake among women of reproductive age (15 to 49 years) in the Yendi municipality in the northern region of Ghana. A health facility-based cross-sectional study was conducted among 396 reproductive-aged women, sampled from 6 randomly selected health facilities in the Yendi municipality. The child welfare clinic (CWC) served as the point for the sampling of study respondents. Data was collected with questionnaires adapted from previously validated tools. Data was analysed using SPSS v27 in descriptive and inferential statistics. More than half of the respondents (54.3%) said they had ever used a family planning method and almost half of them said they were still using a family planning method. The desire to control pregnancy was a key factor for wanting family planning (79.3%). Most respondents (80.6%) had high knowledge of family planning services and injectables (37.1%) and condoms (24.7%) were the preferred family planning methods. The significant sociodemographic determinants of family planning uptake were religion (Christians (aOR: 7.51; 95%CI: 1.48–38.00:; p = 0.015), traditionalist (aOR: 12.1; 95%CI: 1.90–78.36; p = 0.009)), education (secondary education (aOR: 84.99; 95%CI: 20.02–360.84:; p = 0.000), tertiary education (aOR: 158.74; 95%CI: 33.71–747.52; p = 0.000), no formal education (aOR: 11.83; 95%CI: 2.10–46.76:; p = 0.000)), occupation (farmers (aOR: 12.30; 95%CI: 3.21–47.03; p = 0.000)), and marital status (married (aOR: 0.13; 95%CI: 0.03–0.57; p = 0.007)). Factors that made women less likely to use family planning were unfriendly service providers (aOR: 2.33; 95%CI: 1.28–4.21; p = 0.005), fear of side effects (aOR: 2.19; 95%CI: 1.19–4.05; p = 0.012), and lack of knowledge about available FP services (aOR: 0.45; 95%CI: 0.26–0.77; p = 0.004). Though the knowledge of family planning was high, current uptake of family planning services was modest and there are still sociodemographic and health-related barriers to family planning utilization. Highlighting the need for training programs and policy interventions to improve uptake, reduce financial barriers, and foster a supportive environment.